Adoption and Implementation of Balanced Scorecard in Malaysia - Ong, Tze San; Teh, Boon Heng; Lau, Chee Kwong; Wong, Sharon Lee Shyan (2010)
This paper reports the results of an empirical study into the adoption and implementation of Balanced Scorecard in Malaysia. More specifically, it investigates the sequential dependency among the four balances Scorecard (BSC) perspectives, namely learning and growth, internal business process, customer value and financial performance. The findings indicate that organizations responded positively to BSC measures and believed the cause-and-effect relationship of BSC will lead to improved business efficiency and profitability